2017
DOI: 10.1111/1744-9987.12598
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Mortality and Cancer‐Bearing Status in Patients With Chronic Kidney Disease Who Attended an Educational Program

Abstract: Patients with malignancy have a poorer prognosis than others do, which must be taken into consideration when treating them for chronic kidney disease (CKD). However, there are few studies investigating their prognosis. This was an observational study of 515 (394 men and 121 women) stable non-dialysis patients with CKD who attended a CKD educational program. Mean age was 68.8 ± 13.0 years. Median follow-up was 968.5 days. Mean creatinine was 3.4 ± 1.6 mg/dL. Of these, 63 had malignancy and 452 did not; 20.6% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
(18 reference statements)
2
7
0
Order By: Relevance
“…Patients with CKD are often stated in the immunosuppressive status. [ 6 11 , 27 ] The CKD women might impair the ability to eradicate human papilloma virus (HPV) infection when they got infection. In addition, these CKD women subsequently may have a prolonged latency of HPV infection or persistent HPV infection, which is a key factor for the development of cervical pre-cancer lesions and cancers in women.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with CKD are often stated in the immunosuppressive status. [ 6 11 , 27 ] The CKD women might impair the ability to eradicate human papilloma virus (HPV) infection when they got infection. In addition, these CKD women subsequently may have a prolonged latency of HPV infection or persistent HPV infection, which is a key factor for the development of cervical pre-cancer lesions and cancers in women.…”
Section: Discussionmentioning
confidence: 99%
“…The most important strength of the current study was unlikely to the well-known higher risk of upper tract urothelial carcinoma in the CKD women in the world, including Taiwan, [ 6 , 16 , 20 26 , 69 ] and it might be the first nationwide, population-based study to investigate the risk of GC in the CKD women in Asia. In addition, using this national population-based study, we further confirmed that GC is an age-dependent disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations